Impairment of assets. - International Accounting Standards Committee; International Accounting Standards Committee (London : International Accounting Standards Committee, 1998)
Prescribes the accounting and disclosure for impairment of assets. It replaces or will replace the requirements for the recoverability of an asset.
"June 1998"--Cover.
oif 30/03/15
Loan
Keywords: Assets (Accounting).